HUBUNGAN KEMAMPUAN BERPIKIR KREATIF DAN KRITIS DENGAN PRESTASI BELAJAR MAHASISWA PADA MATAKULIAH KONSEP SAINS II PRODI PGSD IKIP PGRI MADIUN - Gunawan, Imam; Suraya, Selly Nurina; Tryanasari, Dewi (Premiere Educandum, 2014)
Critical thinking in education has been widely practiced following the awareness that it helps a lot the students specifically in science subjects. In accordance with critical thinking ability in science, students who show ability on critical thinking will successfully cope with problems they encounter. Such ability hopefully works in their learning achievement. The objective of this research is to investigate the influence of creative and critical thinking on the achievement of the students of the Department of Primary Education IKIP PGRI Madiun in the class of Science Concepts II. The current study makes use of the descriptive correlational. As many as 191students enrolled the class of science concepts II in the academic year 2012/2013, out of 366 populations, serve as the sample through the proportional random sampling technique. Tests were administered to collect the data analyzed by applying descriptive analysis of double regression to assess the hypothesis in which SPSS PASW Statistics 18 was applied. Results show that there is significant correlation on the variables of creative and critical thinking on their achievement. The creative thinking contributes 20.13% while the critical thinking contribution is 21.53%. Other variables beyond this research contribute 58.34%.Key words: Creative Thinking Ability, Critical Thinking, Student Achievement